2011
DOI: 10.4018/ijnmc.2011070102
|View full text |Cite
|
Sign up to set email alerts
|

Citrate Stabilized Silver Nanoparticles

Abstract: Citrate stabilized silver (Ag) colloidal solution were synthesized and characterized for crystallographic and surface properties by using transmission electron microscopy (TEM) and zeta potential measurement techniques. TEM investigation depicted the size of Ago ranges from 5 to 50 nm with smaller particles having single crystal structure while larger particles with structural defects (such as multiply twinned, high coalescence and Moire patterns). ?-potential measurement confirms the presence of Ag+ in nAg st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Battharai et al was able to show the presence of Ag 0 by performing a TEM investigation. Additionally, the existence of Ag + adsorbed on Ag 0 was discovered, and it was established that as Ag ions coalesce, as they formed AgNPs carrying an extra positive charge, which was that of Ag + [ 42 ]. Similarly, this occurs in AgNPs that contain mixtures of Ag 0 and Ag + ; as Ag + coalesces into larger Ag particles, these new particles become positively charged.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Battharai et al was able to show the presence of Ag 0 by performing a TEM investigation. Additionally, the existence of Ag + adsorbed on Ag 0 was discovered, and it was established that as Ag ions coalesce, as they formed AgNPs carrying an extra positive charge, which was that of Ag + [ 42 ]. Similarly, this occurs in AgNPs that contain mixtures of Ag 0 and Ag + ; as Ag + coalesces into larger Ag particles, these new particles become positively charged.…”
Section: Introductionmentioning
confidence: 99%
“…The strong ionic presence in the solution after filtration was responsible for the peak shift. Furthermore, the presence of three species in an AgNP solution is important, as we propose a new mechanism for how each of these three species interacts with the bacterial cell [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown that AgNP surfaces adsorb Ag+ ions in silver colloidal solutions. Our final solution contained three species of silver: Ag0 (AgNPs), Ag+ (silver ions), and Ag0/Ag+ (Ag+ adsorbed on Ag0) [ 2 , 95 ]. The presence of AgNPs was documented by transmission electron microscopy (TEM) imaging [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the functionalization of metal nanoparticles with biomolecules is a limitation due to the absence of capping [30]. Similar reports on silver nanoparticle synthesis while using sodium borohydride have shown that it causes instability in nanoparticles and leads to aggregation via coalescence phenomena [31]. Gold nanoparticles that are synthesized only with NaBH 4 require controlled synthetic conditions like stirring in the dark for one hour and further storage at 4 • C for stable nanoparticles [32].…”
Section: Uv-vis-nir Measurementsmentioning
confidence: 99%